Peran Manajemen Kantor Hukum Dalam Proses Audit Hukum Terkait Pengawasan Pemilihan Sebagai Bentuk Optimalisasi Peran Bawaslu Dalam Menjamin Keterbukaan Dan Akuntabilitas - Vina Amelia; Mega Dewi Ambarwati (JURNAL ILMIAH NUSANTARA, 2025)
This research examines the role of legal audit in supporting election supervision by the Election Supervisory Body (Bawaslu). Legal audits serve as a tool to ensure compliance with election regulations, detect violations, and increase transparency in the election process. This research finds that the integration of legal audits can increase the effectiveness of Bawaslu supervision and strengthen public trust in election results. Therefore, strengthening the capacity of Bawaslu personnel and collaborating with other legal institutions is very necessary to optimize the implementation of legal audits in election supervision.